Disability of motivation-semantic sphere in patients with diabetes mellitus - Burovska, Irina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
Psychological researches that reveal the essence of disorders of the motivational and semantic sphere in patients with diabetes mellitus are considered. Understanding the disease as a complex of somatic and psychological dysfunctions gives the opportunity to develop effective methods of support for chronically ill persons, to reveal the essence and to analyze the disorders of the motivational and semantic sphere in this group of persons. Particular attention is paid to the study of the aspect of intrinsic motivation, as extrinsic motivation is already present in the form of a disease with which one must learn to live. The stages of intrinsic motivation in patients with diabetes mellitus are examined in detail, the disorders that occur on each of them are identified and analyzed. The peculiarities of patients’ motivational and semantic sphere as one of the most important personality substructures have been determined. The semantic sphere of personality and the basis of personal meaning (by D. O. Leontiev) are considered. The main directions of the study of diabetes as a psychosomatic disorder are described and analyzed, which makes it possible to search for harmonious adaptation of the patient in society and individual motives for leaving the disease. The analysis of the dynamics of the motivational – semantic sphere in patients with diabetes mellitus was carried out within the framework of scientific search of psychodynamic researchers, which gives an opportunity to understand the disease as a complex of somatic and psychological dysfunctions. Possibilities of positive psychotherapy and its role in the motivational and semantic sphere for patients with diabetes mellitus are considered. The focus of our view on psychological disorders is related to illness and the important role of physicality in blocking the semantic aspect in this category of patients. The prospects for further exploration and the need for comprehensive research in this problem area.